Secret Agent Jack Stalwart. [book 3], The Mystery of the Mona Lisa : France - Singer Hunt, Elizabeth (Red Fox, 2006)
The Mona Lisa, the most famous painting in the world, has been stolen from the Louvre museum in Paris. Can Secret Agent Jack Stalwart find it before an evil thief takes it out of the country, never to be seen again?